# Given -4(x - 5) = -30, then what is - 2x + 3 ?

### 4 Answers | Add Yours

You should open the brackets using the distributive such that:

`-4x + 20 = -30`

Notice that you may write `-4x + 20` using the group of terms -`2x+3` such that: `-4x + 20 = -2x + 3 - 2x + 3 + 14` .

Hence, `-2x + 3 - 2x + 3 + 14 = -30`

Notice that the group of terms occurs two times such that:

`2(-2x+3) = -30 - 14 =gt 2(-2x+3) = -44`

Dividing by 2 yields:

`-2x + 3 = -22`

**Hence, evaluating -2x + 3 yields `-2x + 3 = -22` .**

You are given that -4(x-5) = -30. So first, we must solve for x in this equation.

-4(x - 5) = -30

-4*x - (-4)(5) = -30 Distribute -4 to everything in the

parenthesis

-4x + 20 = -30 Simplify

-4x + 20 - 20 = -30 - 20 Use inverse operations to solve for x. The inverse of addition is subtraction

-4x = -50 Simplify

-4x/-4 = -50/-4 The inverse of multiplication is division

x = 50/4 = 25/2 Simplify; remember neg/neg = positive

Now substitute the value of x into the second equation and solve:

-2(25/2) + 3

-50/2 + 3

-25 + 3

-22

Therefore, the value of the second equation is -22.

We are given that -4(x - 5) = -30.

-4(x - 5) = -30

=> -4x + 20 = -30

=> -4x = -50

=> x = 25/2

The value of -2x + 3 = -2*25/2 + 3 = -25 + 3 = -22

**The required value of -2x + 3 = -22**

For this reason, we'll remove the brackets from the 1st equation:

-4x + 20 = -30

-4x = -30 - 20

-4x = -50

x = -50/-4

x = 12.5

We'll calculate - 2x + 3 :

- 2x + 3 = -25 + 3 = -22

**The value of the expression - 2x + 3 is - 2x + 3 = -22.**